Pelatihan Pembuatan Stik Sawi Guna Menunjang Inovasi Produk Di Kelompok Wanita Tani (KWT) Dewi Fortuna - Shafira Salsabilla; Arde Agung Hidayatulloh; Yudha Adriansa; Dewi Khrisna Sawitri (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Based on Law No. 20 of 2008, MSMEs are referred to as business activities that stand independently in the form of groups or individuals which are not business activities of a branch company. MSMEs play a very important role in the lives of Indonesian people because many Indonesians make a living from selling through MSMEs. There are still many problems that occur in the world of MSMEs in Indonesia, one of which is the lack of product innovation by MSMEs. There are still many MSMEs that only produce food that has spread widely in Indonesia so that the resulting competitive value is very tight between MSMEs. With these problems to help solve the problems faced by MSMEs, a product innovation assistance is held. This assistance is carried out to create a new product innovation in the form of mustard sticks which will later become the newest product in the Fostered MSMEs.